2014
DOI: 10.1002/jlcr.3178
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cellular uptake ofp-[123I]-phenyl-amino-thiazole (123I-PAT) as a potential agent for targeting tubulin polymerization in tumors

Abstract: The phenyl-amino-thiazole (PAT) templates of methoxylbenzoyl-aryl-thiazole are potent agents against cancer by inhibiting tubulin polymerization in the nanomolar range. Herein, a radioiodinated PAT, [(123)I]-PAT 1, was prepared via a tributylstannyl precursor and [(123)I]iodide through electrophilic aromatic radioiodination. Radiolabelling of [(123)I]-PAT 1 was achieved in less than 15 min, with a radiochemical purity of over 99%. The accumulated radioactivity in tumor cellular uptake experiments suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Meanwhile, some researchers have reported aryl thiazole compounds that can disrupt tubulin polymerization, thereby inhibiting the production of functional MTs and cell mitosis [26]. Thiazole also improves the water solubility and pharmacokinetic parameters of the drugs itself [26,27]. Based on the aforementioned results, we proposed in this work that theintroduction of thiazole moiety into shikonin may improve its water solubility and tumor targeting.…”
Section: Introductionmentioning
confidence: 86%
“…Meanwhile, some researchers have reported aryl thiazole compounds that can disrupt tubulin polymerization, thereby inhibiting the production of functional MTs and cell mitosis [26]. Thiazole also improves the water solubility and pharmacokinetic parameters of the drugs itself [26,27]. Based on the aforementioned results, we proposed in this work that theintroduction of thiazole moiety into shikonin may improve its water solubility and tumor targeting.…”
Section: Introductionmentioning
confidence: 86%
“…20 Some researchers have indicated that aryl dihydrothiazole compounds can also disrupt tubulin polymerization, therefore inhibiting the production of functional microtubules and cell mitosis. 21 For this purpose, we synthesized a series of novel aryl dihydrothiazol acyl podophyllotoxin ester derivatives and evaluated their anticancer activities. We hope our study will pave the way for exploring new anticancer mechanisms of podophyllotoxin derivatives.…”
Section: Introductionmentioning
confidence: 99%